Developmental trajectories of externalizing behavior from ages 4 to 12: Prenatal cocaine exposure and adolescent correlates. (1st November 2018) - Min, Meeyoung O.; Minnes, Sonia; Park, Hyunyong; Ridenour, Ty; Kim, June-Yung; Yoon, Miyoung; Singer, Lynn T.
Highlights: Prenatal cocaine exposure (PCE) is associated with externalizing behavior problems. Four trajectories of externalizing behavior were identified in children with PCE. PCE and maternal psychological distress differentiated different trajectories. Adolescent substance use and early sexual behavior differed by the trajectories. Abstract: Background: Although prenatal cocaine exposure (PCE) has been linked with greater externalizing behavior, no studies have investigated heterogeneity of developmental trajectories in children with PCE to date. The present study aimed to: (1) identify developmental trajectories of externalizing problems in childhood by using a person-oriented analytic approach; (2) examine whether trajectories differ by PCE and other environmental and biological correlates; and (3) investigate how trajectories were associated with adolescent substance use and sexual behavior. Methods: Adolescents ( N  = 386; 197 PCE, 187 non-cocaine exposed (NCE)), primarily African-American and of low socioeconomic status, were prospectively enrolled in a longitudinal study at birth. Externalizing problems were assessed with the Child Behavior Checklist (CBCL) at ages 4, 6, 9, 10, 11, and 12. Substance (tobacco, alcohol, marijuana) use, via self-report and biologic assays, and early (before age 15) sexual intercourse were assessed at age 15. Results: Latent class growth modeling indicated four distinctive developmental trajectories of externalizing behavior from ages 4 to 12: low-decreasing group (32%); moderate-decreasing group (32%); accelerated risk group (14%); and elevated-chronic group (22%). PCE and maternal psychological distress interactively differentiated developmental trajectories of externalizing behavior, which were related to subsequent adolescent substance use and early sexual behavior differently across gender. Conclusions: The two high-risk trajectories (accelerated risk and elevated-chronic groups), comprising 36% of the sample, identified in the present study may reflect multi-causality of early substance use and perhaps greater risk for transition to substance use disorders later in development.